Evaluasi Model Struktural Produktivitas Guru Dengan Sem-Pls: Studi Tentang Kepemimpinan Transformasional dan Motivasi Kerja - Siti Julaeha; Dedy Yusuf Aditya; Asep Saefullah Kamali (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to analyze the influence of transformational leadership on teacher work productivity, both di-rectly and indirectly through work motivation. A quantitative approach was employed using path analysis based on Structural Equation Modeling (SEM) with SmartPLS 4. The population in this study consisted of civil servant elementary school teachers in Tasikmalaya Regency. The results revealed that transformational leadership sig-nificantly influenced teachers' work motivation, with a path coefficient of 0.919 and a p-value of 0.000. Trans-formational leadership also had a significant effect on teacher productivity both directly (coefficient 1.018; p-value 0.000) and in total effect (coefficient 0.954; p-value 0.000). However, work motivation did not have a sig-nificant impact on teacher productivity (coefficient -0.069; p-value 0.815), nor did it serve as a significant media-tor between transformational leadership and teacher productivity. These findings suggest that strengthening transformational leadership practices directly contributes more to improving teacher productivity than relying on motivational pathways.